2013
DOI: 10.1007/s00259-013-2421-z
|View full text |Cite
|
Sign up to set email alerts
|

Standardized added metabolic activity (SAM) IN 18F-FDG PET assessment of treatment response in colorectal liver metastases

Abstract: (18)F-FDG PET imaging is a useful tool to assess treatment response and predict clinical outcome in patients with mCRC who undergo chemotherapy before liver metastasectomy. Follow-up SUVmax, follow-up SAM and ∆SAM were found to be significant prognostic factors for PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
27
1
Order By: Relevance
“…The PET/CT findings led to a change in therapeutic strategy to salvage radiation therapy extended to include the pelvic lymph nodes. After treatment, PSA decreased to 0.3 ng/ml, and at the time of this report he was still progression-free EBRT external beam radiation therapy, ADT androgen deprivation therapy, CTE chemotherapy, HIFU high-intensity focused ultrasound dependence, are of major interest [33]. SAM with FDG is a marker derived from TLG which takes into account metabolic activity as well as lesion volume [34].…”
Section: Discussionmentioning
confidence: 98%
“…The PET/CT findings led to a change in therapeutic strategy to salvage radiation therapy extended to include the pelvic lymph nodes. After treatment, PSA decreased to 0.3 ng/ml, and at the time of this report he was still progression-free EBRT external beam radiation therapy, ADT androgen deprivation therapy, CTE chemotherapy, HIFU high-intensity focused ultrasound dependence, are of major interest [33]. SAM with FDG is a marker derived from TLG which takes into account metabolic activity as well as lesion volume [34].…”
Section: Discussionmentioning
confidence: 98%
“…Several papers have reported correlations between SUV max and the prediction of survival in patients with gastrointestinal cancer . A few clinical and laboratory studies have examined the prediction of prognosis in patients undergoing FOLFOX chemotherapy using 18 F‐FDG PET/CT . However, most studies have only compared the difference in SUV between baseline 18 F‐FDG PET/CT and during chemotherapy; furthermore, these studies mostly enrolled patients with inoperable metastatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have indicated that the optimal morphological response, evaluated using CT, was useful as a subjective evaluation of chemotherapy's effect. 26,27 Mertens et al 28 reported the utility of FDG-PET for CRLM cases that involve chemotherapy before hepatectomy, with the change in the standardized metabolic activity reflecting a poor posttreatment prognosis. Nevertheless, the SUV change ratio is more objective than the optimal morphological response or standardized metabolic activity and may be a novel method for predicting prognosis before preoperative chemotherapy.…”
Section: Associations Of Recurrence and Prognosis After Conversion mentioning
confidence: 99%